¿Es el factor de crecimiento nervioso (NGF) un marcador útil durante el embarazo para la predicción de preeclampsia precoz? - Sepúlveda-Martínez, Álvaro; Romero O., Carmen; Vega I., Margarita; Parra-Cordero, Mauro (Revista Hospital Clínico Universidad de Chile, 2014)
Preeclampsia is one of the major causes of maternal and perinatal death, mainly in the severe early-onset presentation. Second trimester uterine artery Doppler has been demonstrated to be the most sensitive isolated predictive marker of early-onset preeclampsia. However, consistent evidence demonstrated that preventive therapies (aspirin or antioxidants) are not useful during mid-gestation. First trimester uterine artery Doppler has lower sensitivities for severe preeclampsia than second trimester measurement, but by performing a combined predictive model (uterine artery Doppler, biochemical angiogenic markers such as Placental Growth Factor, mean arterial blood pressure and maternal history) the sensitivity is significantly improved. Moreover, recent meta-analysis demonstrated that preventive therapies such as aspirin are useful only when begins before 16 weeks. The Nerve Growth Factor (NGF) is a member of the neurotrophin family with an important role in the development of cholinergic neurons. Recent studies demonstrated that NGF is a potent angiogenic factor in non-neurologic tissues. Patients with preeclampsia demonstrated decreased plasma levels of NGF immediately before delivery. The aim of this review is to evaluate the potential role of NGF as a biochemicalmarker of altered angiogenesis during pregnancy for prediction of early-onset preeclampsia